Analisis Pemahaman Pelaku UMKM terhadap Inklusi Keuangan Syariah dalam Memperluas Akses Pembiayaan di Kelurahan Harjosari Kecamatan Medan Amplas - Asty Amanda; Eli Agustami; Nurhudawi Nurhudawi (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This study aims to analyze the understanding of Micro, Small, and Medium Enterprises (MSMEs) in Harjosari II Village regarding Islamic financial inclusion and its contribution to expanding access to business capital financing. Although the national financial inclusion index continues to increase, the implementation of Islamic financial inclusion still faces challenges at the grassroots level. This research used a descriptive qualitative method with data collection techniques consisting of observation, documentation, and in-depth interviews with MSME owners in Harjosari II Village and staff from KSPPS & BMT Syariah Sejahtera (SS) Medan. The findings show that MSME owners’ understanding of Islamic financial inclusion is influenced by religiosity and the perception of justice through the profit-sharing system. Islamic financial inclusion is implemented through a kinship approach and simplified administrative procedures for the informal sector. However, the main obstacles to expanding financing access include limited Islamic financial literacy, restricted financing ceilings, and entrepreneurs’ lack of confidence in formal banking procedures. Islamic financing contributes to increasing production capacity and providing spiritual peace of mind by offering capital alternatives free from usury (riba). This study recommends strengthening direct technical socialization and implementing more flexible financing ceiling policies to support MSME growth in suburban areas.